Antimicrobial Activity and Cyto‐Compatibility of Plasma Polymerized Zinc Acetylacetonate Thin Films. Issue 3 (21st December 2012) - Malzahn, Kerstin; Duque, Luis; Ciernak, Peter; Wiesenmüller, Steffi; Bender, Katja; Förch, Renate
Abstract Plasma polymerized thin films deposited from zinc acetylacetonate in a low pressure RF capacitively coupled plasma reactor have been studied to correlate the zinc content to the metal ion release properties, antimicrobial activity and cytocompatibility. Zinc content and zinc release properties were studied using inductively coupled plasma optical emission spectroscopy (ICP‐OES) and results were correlated to those from different standard methods of surface analysis. The coatings were shown to act as a zinc reservoir, allowing for a fast release of zinc within a few hours of being in contact with aqueous solution. For all films studied a log 106 reduction in the growth of Staphylococcus aureus was observed. The results show the films to be cyto‐compatible towards NIH 3T3 mammalian cells up to a zinc content of about 5 µg/cm2. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>